Pucking ever after, volume 2 eaudiobook - Rath, Emily (Jacksonville Rays, 2024)
From the international bestselling Jacksonville Rays Hockey series comes a second happily ever after novella! "Come on daddy . . . don't make me beg." "I can't breathe for wanting you. I have no pride left." "Mars . . . do you love me?" Contains mature themes.